2021
DOI: 10.1155/2021/2195238
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative Effects of Gallic Acid on Cisplatin-Induced Nephrotoxicity in Rat Variations of Biochemistry, Histopathology, and Gene Expression

Abstract: Background. Cisplatin is a powerful chemotherapeutic drug mainly used in the treatment of solid tumors. Aggregation of the drug in renal proximal tubule cells causes nephrotoxicity and renal failure. Investigations showed nephrotoxicity as Cisplatin’s dose-limiting side effect. One of the Cisplatin toxicity mechanisms is generation of reactive oxygen species, which leads to oxidative stress and renal damage. The purpose of this study was evaluation of the modulating effects of Gallic acid on Cisplatin-induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 71 publications
2
11
0
Order By: Relevance
“…Naringin has been found to suppress metabolic features and improve the number of functional β cells in rats [ 30 , 31 ]. Epigallocatechin gallate (EGCG) could inhibit 11βHSD1 activity and reduce cortisol levels [ 32 , 33 ], improve metabolic features and insulin sensitivity in animals [ 34 ], and renal histology [ 35 , 36 , 37 ]. p -coumaric acid could inhibit insulin resistance and increase adiponectin levels [ 38 , 39 ] Therefore, it is likely that phenolic compounds contained within KH contribute to the inhibition of MetS risk demonstrated in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Naringin has been found to suppress metabolic features and improve the number of functional β cells in rats [ 30 , 31 ]. Epigallocatechin gallate (EGCG) could inhibit 11βHSD1 activity and reduce cortisol levels [ 32 , 33 ], improve metabolic features and insulin sensitivity in animals [ 34 ], and renal histology [ 35 , 36 , 37 ]. p -coumaric acid could inhibit insulin resistance and increase adiponectin levels [ 38 , 39 ] Therefore, it is likely that phenolic compounds contained within KH contribute to the inhibition of MetS risk demonstrated in this study.…”
Section: Discussionmentioning
confidence: 99%
“…However, improving liver function, restoring antioxidant levels, reducing inflammatory response, and reducing apoptosis can be useful in this case [20]. Previous studies found that antioxidants such as gallic acid, rosmarinic acid, and L-glutamine and selenium had the potential to reduce oxidative stress in the liver and kidney tissues and improve the function of these organs [21][22][23][24][25]. In our study, RIR increased the level of MDA, NO, and liver enzymes such as ALT, ALP, and AST, decreased activity of CAT and GPX, and decreased the level of GSH in liver tissue.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, the major site of cisplatin accumulation in the nephron is the proximal tubules [ 24 , 25 , 26 ]. The entry of cisplatin into the tubular epithelial cells is thought to be mediated by two receptors: Crt1 and OCT2 (copper transporter 1 and organic cation transporter 2) [ 17 ].…”
Section: Major Molecular Mechanisms Of Cisplatin-induced Kidney Injurymentioning
confidence: 99%